Expanding ESL Students’ Vocabulary Through TikTok Videos - Audrey Valeria Bernard (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2021)
TikTok is a video-sharing social network that has abruptly gained popularity for the past few years due to its unique feature of short-form videos on various genres particularly comedy and performance. The videos produced from this platform have been used widely in multiple contexts including classroom teaching. Thus, this project delved into the role of TikTok in capturing students’ attention and introducing them to new vocabulary during English language class through some selected videos from the app. Most students could barely pay attention to their teachers during physical classes or online lessons. This could possibly hinder them from participating actively in classroom activities. Due to the nature of TikTok videos that are shorter in duration with humorous yet informative content, these videos might serve as engaging teaching materials. The results showed that the students displayed improved level of attention, interest and understanding of the subject matter that was being taught in class through TikTok videos. It is recommended that more studies should be done to analyze the multiple types and genres of TikTok videos and how these variables influence students’ learning.